Memoria : Poems - Menes, Orlando Ricardo (Book collections on Project MUSE., 2019)
Born to Cuban parents in Lima, Peru, raised in Miami among political exiles, and having spent two years in Francoist Spain, Orlando Ricardo Menes pays tribute to the resilience and tradition that shape Hispanic culture across the globe while critiquing the hypermasculine characteristics embedded within. Ripe with pride and shame, beauty and aversion, Memoria relays the personal path one takes while navigating the complexities of heritage.